THE INFLUENCE OF CURRENT RATIO, DEBT-TO EQUITY RATIO, AND TOTAL ASSET TURNOVER, AND THEIR IMPACT ON THE PROFITABILITY OF INDONESIAN COAL MINING ENTERPRISES - Arsyadana , Refo; Ridwan, .; Pratiwi , Annissa (Australian Finance & Banking Review, 2025)
This study aims to assess the influence of the current ratio (CR), debt-to-equity ratio (DER), and total asset turnover (TATO) on profitability, as measured by Return on Assets. A quantitative method was used in this study, with a causal research design. The research was conducted on Coal Mining Firms in public enterprises registered at the Indonesia Stock Exchange (IDX), covering the period 2018-2024. A purposive sampling technique is used, yielding a final sample of 25 firms. Documentation is a data collection technique using secondary data from each enterprise's annual report. Processing data with multiple linear regression analysis. These findings suggest that the current ratio and debt-to-equity ratio variables have a positive and significant impact on profitability. The total asset turnover variable has a negative, but non-significant, impact on profitability. The contribution of company profitability with return on assets measurement is 43.7 percent, which is influenced by the three variables, namely Current Ratio, Debt-to Equity Ratio, and Total Asset Turnover, where DER proxy is the main factor considered to see its impact on the Return on Assets in 25 firms that are determined to be samples in this study. Companies should also more effectively and efficiently manage the use of their assets and liabilities, and increase sales growth to minimize the possibility of financial risk and achieve maximum profit. After the pandemic ends, the Government must be more strategic in making policies, especially in the mining sector enterprises listed.JEL Classification Codes: C12, G17, M21.